Retreatment With Flow Diverters and Coiling for Recurrent Aneurysms After Initial Endovascular Treatment: A Propensity Score-Matched Comparative Analysis - Li, Wenqiang; Zhu, Wei; Sun, Xinguo; Liu, Jian; Wang, Yang; Wang, Kun; Zhang, Ying; Yang, Xinjian; Zhang, Yisen (Frontiers in Neurology, 2021)
Background Flow diverters and conventional coiling are established modalities for the retreatment of intracranial recurrent aneurysms after initial endovascular treatment. We aimed to compare the efficacy of these techniques. Methods We retrospectively analyzed data for patients with recurrent aneurysms after initial endovascular treatment retreated in our center with either a pipeline embolization device (PED) or conventional coil embolization from January 2012 to July 2020. We performed 1:2 propensity score matching (PSM) using the nearest neighbor method. We controlled for: initial treatment strategy, aneurysm size, neck diameter, symptom presentation, history of aneurysm rupture, age, sex, fusiform-dissecting aneurysm, bifurcation aneurysm, and aneurysm location. The clinical and morphological factors of all patients at initial treatment and the angiographic and clinical results at the second treatment were collected and compared between the propensity-matched pairs. Results A total of 105 intracranial aneurysms were identified; 18 patients (17.1%) were treated with a PED, and 87 (82.9%) were treated via conventional coil embolization. PSM resulted in 12 matched pairs (12 patients in the PED group and 24 in the coiling group). There was no significant difference of ischemic and hemorrhagic complications between the groups, the obliteration rate of branches covered by stent, or modified Rankin Scale scores at the last clinical follow-up. Importantly, the retreatment strategy in the PED group provided significantly different results vs the coiling group (P< 0.001), with a lower recurrence rate (0.0% vs 29.2%, respectively; P=0.037). However, the procedural failure rate and the parent artery stenosis were more frequently in PED group compared with coiling group. (both were 16.7% vs. 0.0%; P=0.040) Conclusions Endovascular retreatment for recurrent aneurysms after initial endovascular treatment might be safe and effective. Flow diverters might be associated with reduced risk of recanalization and an increased risk of procedural failure and mild parent artery stenosis.